Traditional or Active Learning Methods in Financial Education? A Randomized Controlled Trial - Gudjonsson, Sigurdur; Kristinsson, Kari (Pedagogika, 2025)
The purpose of this study is to compare how much students learn using two different teaching methods under blinded experimental conditions. That is, comparing traditional lectures to active learning. We measure student learning by varying teaching methods during a review for an exam, which was taught either through a 40-minute traditional lecture or a 40-minute session of active learning. The results suggest no difference in learning outcomes between students who received review through active learning and those who received review through traditional means.